Quality of packed baby kiwi cultivar ‘Hortgem Tahi®’ and ‘Hortgem Rua®’ - Giuggioli, Nicole Roberta; Baudino, Claudio; Briano, Rossella; Peano, Cristiana (Progress in Nutrition, 2019)
Baby kiwi fruits (Actinidia arguta) represents a relatively new product in the fresh italian market and the crop is grown in recent years. They are similar to berries and their storage period is different from other kiwi. The aim of this work is to evaluate the evolution of some quality parameters of packaged fruits of two cultivar actually marketed under the Nergi® brand (Hortgem Tahi®and Hortgem Rua®). We monitored weight loss, colour, total soluble solid content, titratable acidity, dry matter, firmness, textural parameters and total polyphenol content of fruits stored at low temperature (1±1°C) up to 60 daysWe can state that baby kiwi are very susceptible to pulp firmness decrease. Generally samples of cv Hortgem Tahi® and Hortgem Rua® packed with the lid have maintained an higher pulp if compared with the control values. The stability of the peel colour and the limiting of the weight losses during the whole storage period are successfully preserved in this preliminary study.